Synthesis and Characterization of Ni2+, Cu2+ and Zn2+ Complexes with Benzimidazole-2-thionate, Diphosphene and Their Reaction with Iodine - Buttrus, N.H.; Mohamed, S.M.; Sabah, A.A.; Abdalrazaq, E.A. (Asian Journal of Chemistry, 2013)
Nickel, copper or zinc metal react with bis-benzimidazole disulfide (C14H10N4S2) (L1) in refluxing ethanol-toluene to give the complexes of the type [M(L)2], where M = Ni2+, Cu2+, Zn2+ and L = benzimidazole-2-thionate (C7H5N2S–) through an oxidative addition reaction. The complexes of type [M(L)2Ph2P(CH2)nPPh2], n= 1, 2 or 3, were prepared by direct reaction of [M(L)2] with diphosphene ligand in (1:1) and (2:2) molar ratio respectively. The reaction of some of the above complexes with iodine was also carried out. The complexes were characterized by microanalysis, IR, UV-visible spectroscopy, molar conductivity and magnetic moment and solid state electrical conductivity measurements. Electronic and magnetic measurements indicate that some of the complexes have square planar geometry and the other contain tetrahedral and octahedral geometries. Solid state electrical conductivity of compact pellets suggest that the complexes are non conducting while with the iodinated complexes behave as typical semiconductors as their conductivities were found to increases with temperature.